STRATEGI PENINGKATAN MUTU PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH SALAFIYAH AL TARMASI - Asep Sunarko; Sholeh Sholeh (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2018)
Learning Arabic for the world of the Salaf Islamic Boarding School, which focuses on the study of the Yellow Book is one of the most important foundations because without understanding Arabic properly, it will face many difficulties. The learning system in Islamic boarding schools is often called Madrasah Diniyah. This Madrasah is one of the religious education institutions on the outside school path, which is expected to be able to continuously provide Islamic religious education to unmet students on the school path through the classical system. To study this problem, this research was carried out in the Madrasah Diniyah Al-Tarmasi with the subject of madrasah management from the Madrasah Headmaster, the board of teachers and education staff as well. Collecting data in this study are used interviews, observation and documentation as the main instruments with data triangulation as the analytical knife. The results of the study shown that there are several efforts by the Headmaster of Madrasah and teachers in improving the Quality of Arabic language learning by pouring a number of Strategies in: 1) Strategies to improve curriculum and the process of Arabic learning. 2) Strategies for improving the quality of human resources to improve Arabic learning. 3) Strategies for improving the quality of facilities and infrastructure to improve the quality of Arabiclearning.